Integrating organizational impacts into health technology assessment (HTA): an analysis of the content and use of existing evaluation frameworks. (2nd November 2022) - Pascal, Christophe; Mathy, Caryn; Bongiovanni, Isabelle; Konishi, Mario
Abstract: Objective: The French health technology assessment (HTA) agency initiated a research between 2018 and 2019 with the aim of determining whether other HTA organizations (agencies, bodies, institutes, and expert networks) and researchers had developed an evaluation framework of organizational impacts (OIs). Methods: Three types of investigation were carried out: (i) an analysis of documents published by selected HTA organizations, (ii) a rapid review on the OI issues, (iii) a questionnaire survey to experts of the International Network of Agencies for Health Technology Assessment. Results: The analyses highlight six key points: (i) there is no explicit conceptual definition of OIs; (ii) OIs are often not included in a specific dimension of the evaluation or in the same dimensions; (iii) three recurring categories emerge from the assessment of OIs: processes, structure, and culture; (iv) despite its limitations, the European Network for Health Technology Assessment framework (Core Model) is the most mature assessment model to date; (v) the question of the scope of OIs to be considered is unresolved (micro-meso-macro); and (vi) the delineation between OI assessment and economic assessment must be addressed. Conclusions: Although the issue of considering OI in HTA has been raised for many years, it remains largely unresolved. Defining the concept of OI is a prerequisite for taking the next step toward an evaluation framework. As the question of the impact of innovation goes beyond the health sector, extensive research on how to define and take into account these OIs may be relevant.